Effectiveness of Discovery Learning Using TikTok in Enhancing Students’ Creativity in Arabic Speaking Skills - Putri Choirunnisa; Ahmad Tarmizi; Kemas Muhammad; Nurkhamimi Zainuddin (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2026)
The integration of digital technology in 21st-century education demands innovative, student-centered learning, yet Arabic speaking instruction at MI Adabiyah 2 Palembang remains teacher-centered with limited digital media, resulting in low student creativity and participation. Theoretically, discovery learning encourages active knowledge construction and creative thinking, while TikTok provides interactive visual-auditory stimulation. This study aims to determine the improvement in students’ creativity through discovery learning-based speaking instruction using TikTok as a learning medium. A mixed-methods approach with a one-group pretest-posttest design was employed, involving 28 fourth-grade students. Quantitative data were collected through pretests, posttests, and creativity questionnaires, while qualitative data were obtained from observations, interviews, and documentation. The results showed that the mean pretest score of 54.29 increased to 82.43 in the posttest, with a paired-sample t-test indicating a significant improvement (p < 0.001). The N-Gain score of 62.48% fell into the moderate or fairly effective category. In conclusion, discovery learning-based speaking instruction using TikTok media is effective in improving students’ creativity. It is recommended that teachers integrate interactive digital media and student-centered models to create more innovative and creative Arabic language learning. Perkembangan teknologi digital dalam pendidikan abad ke-21 menuntut pembelajaran yang inovatif dan berpusat pada siswa, namun pembelajaran berbicara bahasa Arab di MI Adabiyah 2 Palembang masih berpusat pada guru dengan keterbatasan media digital, sehingga kreativitas dan partisipasi siswa rendah. Secara teoretis, discovery learning mendorong siswa aktif membangun pengetahuan dan berpikir kreatif, sedangkan TikTok menyediakan stimulus visual-auditori yang interaktif. Penelitian ini bertujuan untuk mengetahui peningkatan kreativitas siswa melalui pembelajaran berbicara berbasis discovery learning menggunakan media TikTok. Penelitian ini menggunakan pendekatan mixed methods dengan desain one-group pretest-posttest yang melibatkan 28 siswa kelas IV. Data kuantitatif dikumpulkan melalui pretest, posttest, dan angket kreativitas, sedangkan data kualitatif diperoleh dari observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa nilai rata-rata pretest 54,29 meningkat menjadi 82,43 pada posttest, dengan uji paired-sample t-test menunjukkan peningkatan signifikan (p < 0,001). Nilai N-Gain sebesar 62,48% termasuk dalam kategori sedang atau cukup efektif. Kesimpulannya, pembelajaran berbicara berbasis discovery learning menggunakan media TikTok efektif dalam meningkatkan kreativitas siswa. Guru disarankan untuk mengintegrasikan media digital interaktif dan model pembelajaran berpusat pada siswa guna menciptakan pembelajaran bahasa Arab yang lebih inovatif dan kreatif.